Statistical atlases and computational models of the heart : imaging and modelling challenges : 7th international workshop, STACOM 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, revised selected papers /: imaging and modelling challenges : 7th international workshop, STACOM 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, revised selected papers. (2017) - Unknown
No abstract available